Sacbrood Virus: A Growing Threat to Honeybees and Wild Pollinators - Ruike Wei; Lianfei Cao; Ye Feng; Yanping Chen; Gongwen Chen; Huoqing Zheng (Viruses, 2022)
Sacbrood virus (SBV) is one of the many viruses that infect both the Western honeybee (Apis mellifera) and the Eastern honeybee (Apis cerana). Recently, the interspecies transmission of SBV has been discovered, especially among wild pollinators. This newly discovered evolutionary occurrence regarding SBV indicates a much wider host range than previously believed, causing further concern about the future sustainability of agriculture and the resilience of ecosystems. Over the past few decades, vast numbers of studies have been undertaken concerning SBV infection in honeybees, and remarkable progress has been made in our understanding of the epidemiology, pathogenesis, transmission, and manifestations of SBV infection in honeybees and other pollinators. Meanwhile, some methods, including Chinese medicine, have been established to control and prevent sacbrood disease in A. cerana in Asian countries. In this review, we summarize the existing knowledge of SBV and address the gaps in the knowledge within the existing literature in the hope of providing future directions for the research and development of management strategies for controlling the spread of this deadly disease.